Prevalence of Oral Diseases in Patients with Chronic Pancreatitis (Texas Journal of Multidisciplinary Studies, 2022)
The article deals with the variety of clinical signs of chronic pancreatitis, manifested in the mouth. Noted their pathogenic mechanisms, directly dependent on whether the patient has a history of chronic pancreatitis. Identify common patterns of abnormalities in the oral cavity in chronic pancreatitis by comparing the two control groups of patients.